Chitosan–silver nanocomposites as a promising tool for controlling the bed bug: Cimex lectularius (Heteroptera: Cimicidae). (March 2023) - Attia, Marwa M; Khalf, Mahmoud A; Abou-Okada, Mahmoud; Shamseldean, Muhammad SM; Salem, Mai A; Al-Sabi, Mohammad Nafi Solaiman
This study evaluates the use of chitosan–silver nanocomposites (CSN) as an insecticide against the bed bug ( Cimex lectularius ). Adult bed bugs were collected from infested residential areas and identified using light microscopy and scanning electron microscopy. CSN were prepared and photographed for characterization using transmission electron microscopy, dynamic light scattering, and zeta potential. The insecticidal effect of different concentrations of CSN (400–1000 ppm) was compared to that of 0.1% cypermethrin as a positive control and normal saline as a negative control. The bugs ( n  = 25) were immersed for 20 min in the corresponding medium, dried with filter papers, and then incubated at 27–28°C and 70% RH with a 12:12 h light–dark photoperiod. The mortality rates were recorded at different time intervals (2, 4, 6, 12, and 24 h post-incubation (hPI)), and the entire experiment was repeated five times. Image analysis showed round- to spherical-shaped CSN ranging in size from 34 to 72 nm. The mortality rates were positively associated with increasing concentrations of CSN. The mortality rate first reached 100% for concentrations of 800 ppm at 24 hPI and 1000 ppm at 12 hPI. The calculated LC50 was found at a concentration of 1165 ppm at 2 hPI, and the LC99 was found at a concentration of 1914 ppm at 2 hPI. The positive control, cypermethrin, induced 100% mortality among the bugs at 2 hPI, while the negative control caused no mortality. These results clearly show the potential of CSN as an insecticide against C. lectularius . Future studies on best practices for implementing these particles in clinical settings are recommended.